BLOOD DONATION BAN POLICIES AND FUNDAMENTAL RIGHTS OF LGBTQI COMMUNITY: DOES IT NEED A POTENTIAL SOCIO-LEGAL REFORMS FOR INCLUSIVITY? - Singh, Deo Narayan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The current debate on the subject has drawn ample attention of the civil society towards a case pending before the Hon’ble Apex Court comprising of a bench headed by Chief Justice of India D. Y. Chandrachud who has also sought responses from the National AIDS Control Organisation (NACO) and the National Blood Transfusion Council (NBTC). In his petition, Sharif D. Rangnekar, represented by attorneys Rohit Bhatt and Ibad Mushtaq, contested the legality of Clause 12 of the "Guidelines for Blood Donor Selection & Blood Donor Referral, 2017" that were published on October 11, 2017, by the National Aids Control Organization and the National Blood Transfusion Council (NBTC). Thus, Rangnekar requested that the SC order the Centre to create rules permitting homosexual and LGBTQI (lesbian, gay, bisexual, transgender, queer, intersex) individuals to donate blood, subject to appropriate limitations based on "screen and defer" or "assess and test" regulations. The petitioner challenge the ban stating that “It is presumed that a particular group of persons may be suffering from sexually transmitted diseases. Medical technology and education, especially in the field of haematology, has progressed tremendously. The screening of donors is conducted for every donation before a transfusion,” further, it was also claimed by the petitioner that “Today, a blanket prohibition does not stand to reason.